EKSISTENSI PEREMPUAN DALAM TRADISI HARI FATIMAH DI PELAUW MALUKU: KAJIAN FEMINISME SIMONE DE BEAUVOIR DAN FATIMA MERNISSI - Latuconsina, Susi Hardila; Nukuhaly, Nur Apriany; Tuasikal, Rusli (LP2M IAIN Ambon, 2024)
Abstract This study aims to describe the existence of women in the tradition of Fatima Day in the country of Pelauw Maluku Tengah. This type of research is qualitative description with the feminism theory approach of Simone de Beauvoir and Fatima Mernissi with data sources such as documents, videos and interviews. Based on the results of the research, it was concluded that the existence of women in the tradition of Fatima Day as in the procession of Ma’a koku sanama manu and ma’a hu’u uru there was a correspondence with the thinking of Simone de Beauvoir about women and history as well as women of the present. Unlike the Beauvoir feminism, the correspondence of the Fatima day tradition with the thought of the feminist Fatima Mernissi, that is, women participate in the role of reading the Zikir in the Procession of the Sahut and Zikir up Fatima. In addition, women in their daily lives are free to participate and actively participate in the social life, some professing as teachers, lecturers, government officials, private, merchants, students and students. Keywords: Fatimah Day, traditions, women, feminist theory